2002
DOI: 10.1023/a:1016571825025
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Eukaryotic centromeres are composed of centromere DNA and the multiple proteins directly or indirectly associated with it. One important DNA-binding protein in the centromere is DNA topoisomerase II (topo II). In the genome in general, topo II has two functions, one structural and one enzymatic, the latter catalyzing DNA strand-passage reactions. It has been demonstrated that topo II accumulates at centromeres during the first part of mitosis, and disappears again at anaphase, but it has not been clear whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 27 publications
0
25
0
2
Order By: Relevance
“…What is the nature of such catenations and why do they seem to affect only a subset of chromosomes? Given the persistent association of sister centromeres after chromatid arms have separated (Losada and Hirano, 2001;Bernard and Allshire, 2002), and the known accumulation of topoII␣ protein (Rattner et al, 1996;Sumner, 1996) and topoII activity (Floridia et al, 2000;Andersen et al, 2002;Spence et al, 2002;Agostinho et al, 2004) at centromeres, one may reasonably speculate that centromeric catenations are uniquely resolved by topoII␣ and persist after anaphase onset in topoII␣-depleted cells. In the absence of cohesin-dependent centromeric cohesion, poleward forces might then be sufficient to allow near normal separation of sister kinetochores, at the expense of severe chromosomal distortions and DNA damage, resulting in the dissociation of many, but not all, sister chromosomes.…”
Section: Essential Role For Topoii␣ Activity In Chromosome Segregationmentioning
confidence: 99%
“…What is the nature of such catenations and why do they seem to affect only a subset of chromosomes? Given the persistent association of sister centromeres after chromatid arms have separated (Losada and Hirano, 2001;Bernard and Allshire, 2002), and the known accumulation of topoII␣ protein (Rattner et al, 1996;Sumner, 1996) and topoII activity (Floridia et al, 2000;Andersen et al, 2002;Spence et al, 2002;Agostinho et al, 2004) at centromeres, one may reasonably speculate that centromeric catenations are uniquely resolved by topoII␣ and persist after anaphase onset in topoII␣-depleted cells. In the absence of cohesin-dependent centromeric cohesion, poleward forces might then be sufficient to allow near normal separation of sister kinetochores, at the expense of severe chromosomal distortions and DNA damage, resulting in the dissociation of many, but not all, sister chromosomes.…”
Section: Essential Role For Topoii␣ Activity In Chromosome Segregationmentioning
confidence: 99%
“…During metaphase, topoisomerase-II accumulates specifically at active centromeres, where it is required for proper kinetochore͞centromere structure and to decatenate sister chromatids before segregation (19)(20)(21)(22)(23). Decatenation is a three-step process that involves double-stranded DNA cleavage, passage of one strand of the duplex through the break, and religation to repair the lesion.…”
mentioning
confidence: 99%
“…Mapping of deletion chromosomes has delimited the functional centromere region of the human X chromosome to the higher-order alpha-satellite array, DXZ1 (26). Topoisomerase II cleavage activity is found at the active centromere but not the inactive centromere of dicentric chromosomes (28) and has been localized within higher-order arrays of the X (29) and Y (30) chromosome. Chromatin immunoprecipitation (31) and fiber-FISH (32) studies have found higher-order alpha-satellite sequences associated with essential kinetochore proteins.…”
mentioning
confidence: 99%